The Emergence of Bangsawan Dayak in Sarawak - Nur Afifah Vanitha, Abdullah; Nur .Qasdeena Jeeta, Abdullah (Universiti Malaysia Sarawak, 2014)
The bangsawan or also known as the Malay opera was performed in Sarawak by various bangsawan troupes from Malaya and Singapore in the early twentieth century. Its earliest performance in Kuching was performed by the Malay Opera of Malacca, under Wan Yet al- Kaf in 1914. Sarawak natives, especially the Malays and Dayaks, were attracted to bangsawan which emerged as a popular theatre form. Besides patronizing its performances, some joined these troupes either as its part time or full time artist. Gradually in the 1930s bangsawan became as part of Sarawak performing arts and culture. Nevertheless, little is known about the bangsawan performances by the Dayak community. Therefore, the purpose of the article is to capture the development and activities among the bangsawan Dayak from the 1930s to the late 1940s in Sarawak. Performance theory will be applied as an analysis tool to focus on the origin, performance and declination of bangsawan Dayak in Sarawak. Thus, this article discusses on the establishment of bangsawan Dayak in Sarawak and a detailed analysis of its theatrical elements such as the acting style, extra turn, music and program master. Finally, this article discusses thoroughly on the contextual factors that brought the downfall of Bangsawan performances in Sarawak in the late 1940s.